The Wise Old Man In “The Kite Runner” By Khaled Hosseini ; Archetypal Approach - Pegi Fortunela; Tomi Arianto (Cordova Journal : languages and culture studies, 2020)
This research emphasizes on the analysis archetypal image of wise old man that found in Kite Runner novel by Khaled Hosseini in 2003. The novel is flashback story that told about Amir and Hassan as best friend who always play together when they child in Kabul, Afghanistan. The object of the research is archetypal image of wise old man in Kite Runner novel by Hosseini viewed from Carl Gustav Jung theory. The researcher employs qualitative descriptive method to analyze wise old man in Kite Runner novel by Hosseini. Data result founded from primary data and secondary data that stated by Creswell. In doing qualitative research, the researcher employs archetypal image theory purposed by Jung that categorized in book of Guerin (2005) as basic concept and framework thinking. The researcher found Hassan as symbol of wise old man and the realization wise old man of Hassan are as mentor, helpful man and guardian. All those realization wise old man of Hassan in this novel is very impact to support major character reach his goal. From the analysis, it can be concluded the wise old man is compatible to be found in Kite Runner novel by Hosseini.